Green Lifestyle: The Mediating Role of Digital-Based Environmental Awareness on Purchase Intention - Ida Farida Oesman; Ridho Riadi Akbar; Kartika Nuradina (International Journal of Business Economics (IJBE), 2026)
Purpose – This study investigates how a green lifestyle influences the purchase intention of sachet coffee among Generation Z in Bandung City, examining both direct effects and indirect paths mediated by digital-based environmental awareness. This research addresses a critical gap in the literature, as few studies have explored the specific intersection of green lifestyles, digital environmental awareness, and the consumption of instant packaged coffee.Methodology – Utilizing a quantitative research design with a descriptive-verificative approach, data were gathered from 336 respondents selected via purposive sampling. Surveys and structured interviews were deployed for data collection, and hypotheses were tested using Structural Equation Modeling-Partial Least Squares (SEM-PLS).Findings – Results confirmed that all constructs were valid and reliable, except for the Ecological Lifestyle construct, which remained acceptable in certain contexts. A green lifestyle significantly affected purchase intention directly, and indirectly through digital-based environmental awareness.Originality/Novelty – This study introduces novelty by integrating green lifestyle, digital-based environmental awareness, and sachet coffee purchase intention into a single conceptual model focused on Generation Z in Bandung City. The uniqueness of this research is in incorporating digital-based environmental awareness as a mediating variable—an element rarely explored in the context of instant coffee consumption in Indonesia.Implications – This study offers valuable insights for sachet coffee producers, government, and environmental institutions can leverage digital platforms to enhance environmental awareness among Generation Z, an audience highly active in digital ecosystems.